Traumatic subgaleal hematoma drainage in an adolescent: a case report and review of the literature - Aubert, Blandine; Cadoux, Manon; Sahyoun, Cyril (Frontiers in Pediatrics, 2023)
Background: Subgaleal hematoma is a well-known life-threatening complication of instrumentation at birth. Even though most cases of subgaleal hematomas occur in the neonatal period, older children and adults are also at risk for subgaleal hematomas and their complications, following head trauma. Objective: We hereby report the case of a 14-year-old boy who presented with a traumatic subgaleal hematoma requiring drainage, and review the relevant literature regarding potential complications and indications for surgical intervention. Results: Infection, airway compression, orbital compartment syndrome and anemia requiring transfusion are potential complications of subgaleal hematomas. Although rare, surgical drainage and embolization are occasionally required interventions. Conclusion: Subgaleal hematomas following head trauma can occur in children beyond the neonatal period. Large hematomas may require drainage to relieve pain or when compressive or infectious complications are suspected. Although usually not life-threatening, physicians taking care of children must be cognizant of this entity when caring for a patient with a large hematoma following head trauma and in severe cases, consider a multidisciplinary approach.